The Effect of Rewards and Punishment Systems on Employee Work Productivity - Rafli Wahyu Prasetya; Noveria Susijawati; Sandi Nasrudin Wibowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of reward and punishment systems on employee productivity at PT. CB Enterprise, a mid-sized manufacturing company located in Cirebon City, Indonesia. The company has experienced fluctuating productivity levels, which prompted management to explore internal motivational strategies. However, prior to this study, no systematic evaluation had been conducted to determine the actual impact of such mechanisms within the company’s operational context. A quantitative research design was employed involving 100 employees as the total population sample. Data were collected using a structured questionnaire with Likert-scale responses, covering three key constructs: reward system, punishment system, and employee productivity. Each construct was measured using multiple validated indicators. Data analysis was performed using SPSS 26, including validity and reliability tests, classical assumption tests, and multiple regression analysis. The results indicate that the punishment system has a significant and positive effect on employee productivity, suggesting that disciplinary enforcement plays a crucial role in shaping work behavior. Conversely, the reward system showed no statistically significant influence. This does not suggest that rewards are irrelevant, but may indicate a misalignment between current reward strategies and employee expectations, especially regarding non-financial or intrinsic incentives. The findings provide insights into how structured punishment can reinforce productivity in certain organizational cultures, while also highlighting the need to reevaluate existing reward schemes. This study contributes to the broader discourse on human resource practices in Indonesian enterprises and calls for more context-sensitive incentive models in future research.